Migration and Torture in Today’s World, by Fabio Perocco (ed.) - Berta, Giulia (Torture Journal, 2023)
The article is a review of the volume Migration and Torture in Today’s World, curated by Fabio Perocco and published by Ca’ Foscari Editions in 2023.